How do we define therapy-resistant constipation in children aged 4-18 years old? A systematic review with meta-narrative synthesis - Marc A Benninga; Morris Gordon; Carlo Di Lorenzo; Shaman Rajindrajith; Miguel Saps; Vassiliki Sinopoulou; Merit Tabbers; Watshala Hathagoda; Aditi Bhupendra Rane; Anita Sedghi (BMJ Publishing Group, 2024)
Background Therapy-resistant constipation often is a frustrating clinical entity recognised by the persistence of infrequent and painful bowel movements faecal incontinence and abdominal pain despite intensive treatment. It is important to clearly define therapy-resistant constipation before children are subjected to invasive diagnostic and therapeutic procedures.Aim To conduct a systematic review determining how paediatric interventional studies define therapy-resistant constipation.Method We searched CENTRAL, MEDLINE, Embase, WHO ICTR and ClinicalTrials.gov. Studies that included patients with therapy-resistant constipation were identified. Data were extracted on criteria used for defining therapy-resistant constipation and reported using a meta-narrative approach highlighting areas of convergence and divergence in the findings.Results A total of 1553 abstracts were screened in duplicate, and 47 studies were included in the review. There were at least seven definitions used in the paediatric literature to define medically resistant constipation. The term intractable was used in 24 articles and 21 used the term refractory to describe therapy-resistant constipation. Out of them, only 14 articles have attempted to provide an explicit definition including a predefined time and prior therapy. There were 10 studies without a clear definition for therapy-resistant constipation. The duration before being diagnosed as therapy-resistant constipation varied from 1 months to 2 years among studies. Seven studies employed the Rome criteria (Rome III or Rome IV) to characterising constipation while five adopted the Rome III and European and North American paediatric societies definition of paediatric gastroenterology, hepatology and nutrition guideline of management of constipation in children.Conclusion The current literature has no explicit definition for therapy-resistant constipation in children. There is a need for a detailed consensus definition to ensure consistency of future research and to avoid unnecessary and maybe even harmful, invasive diagnostic and therapeutic interventions.